MATHEMATICAL MODELING OF THE PROCESS OF RESORPTION AND SALT DEPLETION BY FILTRATION IN FISSURED ROCK STRATA - A. G. Balamirzoev; E. R. Balamirzoeva; M. R. Magomedova (Вестник Дагестанского государственного технического университета: Технические науки, 2017)
Objectives. A mathematical modeling method is used to describe the process of resorption and salt depletion by filtration through fractured gypsified rock strata.Since the increase in the opening of crevasses due to resorption of their walls from water percolating through rock fractures containing soluble contaminants, a change in the porosity and fracturing of rocks increases filtration rate and Darcy flux leading to foundation subsidence. Method. A process for the simplest schema with a single particulate material filling a fissure of length l and width 2h is examined; the filtration rate is considered constant and equal to v. To solve the resulting parabolic equation the economical difference scheme of alternating directions (convergence formula) is used; this is totally stable and requires simultaneous linear algebraic equations (SLAE) equations with a tridiagonal matrix at each stage of the solution. Results. An algorithm, compiled and programmed to calculate the distribution of concentrations in the fissure using DELPHI programming language, is proposed. Numerical results are summarised due to dissolution concentration distinction in the filled fissure. Conclusion. Using a modified algorithm, the compiled and debugged program using DELPHI programming language allows the distribution of concentrations to be calculated.